UPAYA PENINGKATAN PENGETAHUAN KADER DI WILAYAH PROGRAM KEMITRAAN MASYARAKAT PUSKESMAS LIMO DEPOK TENTANG COVID-19 DENGAN KOMORBID - Hany Yusmaini; Sri Wahyuningsih; Erna Harfiani; Meiskha Bahar (Universitas Majalengka, 2022)
Covid-19 is a disease caused by a new type of viral infection that has never been identified before in humans and can cause lung inflammation. The development of Covid-19 in patients with comorbidities is usually more rapid and severe so it often causes death compared to non-comorbid. Comorbid is a disease that has been owned by a patient before being infected. The accompanying disease can worsen Covid-19 especially if the disease is not controlled. Therefore preventive measures in this group are very important considering that until now drugs and vaccines for this disease have not been found. The confirmed number of Covid-19 in Depok city is quite high. The target of this community service activity is the cadres in the Program Kemitraan Masyarakat area of Limo Depok divided into 4 extension areas : Limo, Meruyung, Krukut, and Grogol. In addition to being provided online with Gmeet, counseling is also provided by sharing videos through WhatsApp groups and pocketbook giving. The implementation of the activity was carried out in September 2020. Evaluation of activities is carried out using pre and post-tests. The result of this activity is a significant increase in cadre knowledge about Covid-19 with Comorbid (p<0.05), which is expected to help increase Covid-19 alertness and prevention measures in at-risk groups in Limo region.